DARIAH.it: Data Integration Strategies and Solutions for Digital Resources Management and Research in the Arts and Humanities - Spadi, Alessia; Degl’Innocenti, Emiliano; Di Meo, Carmen (Mimesis Journal, 2024)
The article details the work carried out within the DARIAH.it research infrastructure, based at the Istituto Opera del Vocabolario Italiano, exploring EU-funded projects such as the SSHOC cluster (www.sshopencloud.eu), EOSC-related activities (specifically, the EGI-ACE project: https://www.egi.eu/project/egi-ace/), and the IPERION-HS project (www.iperionhs.eu). DARIAH.it focuses on enhancing access to cultural resources managed by public cultural institutions and national stakeholders, with an emphasis on data curation and the creation of interoperable ecosystems. The article highlights the design and implementation of the RESTORE project as a successful use case, initially conceived as a research pilot within the SSHOC project consortium, which has since evolved into a functional digital suite to assist humanities and heritage science scholars in data collection and integration. The implemented workflow includes data integration strategies tailored to various digital humanities (DH) disciplines, tools supporting linguistic data workflows, and models that promote resource interoperability, reuse, and sustainability within the humanities and cultural sectors.